Facile synthesis of Schistose-like Co-Mn oxides for low-temperature catalytic oxidation of NO with enhanced SO2/H2O tolerance. Issue 6 (December 2022) - Cheng, Xiaomin; Wang, Xiao; Ma, Cheng; Wang, Jitong; Qiao, Wenming; Ling, Licheng
Abstract: The schistose-like Mn-Co oxides were synthesized by thermal decomposition of inorganic salts as catalyst for NO oxidation. The morphological and surface structural properties can be efficiently regulated by controlling the ratio of Co/Mn. Schistose-layered structure with plentiful nanopores not only facilitates the exposure of active sites but also improves the diffusion and adsorption of NO. Abundant active oxygen species and highly content of Mn 4+ formed on the surface of Co1 Mn4 play a vital role in the catalytic oxidation of NO. Thus, Co1 Mn4 catalyst achieves the highest conversion rate of 54.4 % at 120 °C and 91.3 % at 240 °C. Moreover, satisfactory long-time stability as well as outstanding tolerance to SO2 and H2 O could be obtained for Co1 Mn4 catalyst. Distinct distinctions on the variation of nitrate/nitrite species over Mn and Co1 Mn4 are discovered by in-situ DRIFTS, which provided basis for elucidating the reaction mechanism. This work broadens the horizons for the design of bimetallic catalysts for low-temperature NO oxidation. Highlights: A facile template-free strategy is used to prepare schistose-like Co-Mn catalysts. Schistose-layered structure facilitates the exposure of active sites and the diffusion of gas. The synergistic effect of Mn and Co not only greatly promotes the formation of nitrate species but also inhibits the competitive adsorption of SO2 . H2 O can change the type of sulfate species and reduce the toxicity of SO2 .